2015
DOI: 10.5336/medsci.2015-46632
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Teleradiology in Turkey: Current Situation and Attitudes of Radiologists

Abstract: A AB BS S T TR RA AC CT T O Ob bj je ec ct ti iv ve e: : In this study, we aimed to evaluate the teleradiology use in the daily practices of the radiologists and the attitudes regarding the use of teleradiology in Turkey. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : The descriptive cross-sectional study was based on a 27-item questionnaire which was administered online and through in-person structured interviews. The questionnaires that were duly filled and returned within one year were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Although the results of these survey studies are not fully comparable due to the different conditions, regulations, and policies among various countries and regions, their technical infrastructure and usage concepts are comparable with global applications. Several remarkable results were obtained in the current study that were not addressed in other surveys, [14][15][16][17] which were not specifically aimed at practicing teleradiologists.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Although the results of these survey studies are not fully comparable due to the different conditions, regulations, and policies among various countries and regions, their technical infrastructure and usage concepts are comparable with global applications. Several remarkable results were obtained in the current study that were not addressed in other surveys, [14][15][16][17] which were not specifically aimed at practicing teleradiologists.…”
Section: Discussionmentioning
confidence: 66%
“…Another limitation of this study is the relatively low number of respondents, who made up approximately 3% of the potential pool. Nevertheless, unlike in similar studies, [14][15][16][17] only radiologists actively performing teleradiology participated in the current study. The country-level participation rates were similar when compared to those of other published surveys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8 In addition, insufficient integration of clinical history was revealed as a common disadvantage of teleradiology. 21 Other key challenges indicated by our sample were access to prior images and the quality assurance of images acquired remotely. These challenges have been reported in other studies as well.…”
Section: Participantsmentioning
confidence: 99%
“…These benefits have also been demonstrated in numerous studies. 6,7,21 In addition, teleradiology has been regarded as beneficial during the COVID-19 pandemic by radiologists in Saudi Arabia. Al-Dahery et al found that most of their participants had a positive view of teleradiology in reducing infection risk during the pandemic.…”
Section: Participantsmentioning
confidence: 99%